Pulmonary hypertension associated with portal hypertension and pulmonary hypertension in sarcoididosis of breathing organs: complex pathogenetic relationships - T. P. Kalacheva; G. M. Chernyavskaya; T. S. Ageeva; I. K. Livshits; V. L. Ostanko; E. V. Bolotova; O. A. Denisova; M. V. Listopadova (Бюллетень сибирской медицины)
In the literature review, modern views on the features of pathogenesis and diagnosis of pulmonary hypertension associated with portal hypertension and sarcoidosis of respiratory organs are presented. A variety of views is due to the lack of a convincing evidence base underlying the algorithm for diagnosis and treatment of this pathology. Pulmonary hypertension is one of the most complex cardiological problems and represents a pathological condition that is based on increasing resistance to blood flow in a small circle of blood circulation at any of site. Unlike the systemic arteries, there is no direct access to the pulmonary artery for measuring blood pressure by non-invasive methods, so the diagnosis of pulmonary hypertension in the early stages, before the formation of a lesion in the target organ, which is the right ventricle of the heart, is practically impossible. In actual clinical practice, pulmonary hypertension is at best diagnosed at the stage of latent right ventricular dysfunction, which is manifested by dilatation of its cavity and / or hypertrophy of its walls, at worst at the stage of right ventricular heart failure. At present, there has been a trend towards an improvement in the diagnosis of pulmonary hypertension (LH) in various diseases. This is the reason for the special interest in this interdisciplinary problem.